Developing English Materials for the Students of Information System Department at Technology and Information Faculty, Mathlaul Anwar University Banten - Rohimajaya, Nur Azmi; Sudirman, Ade; Hamer, Welliam (Language Circle: Journal of Language and Literature, 2021)
The aim to be reached in conducting this study is to develop suitable English materials for the students of the Information System Department at Technology and Information Faculty of Mathlaul Anwar University so that they can study what they need to learn. The development will produce an English textbook (module) that is relevant to the objective of curriculum and the needs of the students. It is expected that lecturers and the students can take advantage of the product of the development. The design of this study is categorized under Research and Development (R&D) with analysis, design, development, implementation and evaluation. From the research that has been done, it can be concluded that the module is developed which is more valid, practical and effective. The analysis of the validity of the module can be seen from the aspect of content and presentation. The future suggestion for other researchers is to develop an English language module specifically for education. Students need a special book that is more relevant to be a reference for using English in the context of teaching. Because English is an international language, English course in the Information System Department is expected to contribute to all aspects of life, especially when the students graduate from university